2022
DOI: 10.1021/acs.jcim.2c01352
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Dominant SARS-CoV-2 Variants

Abstract: Accurate and reliable forecasting of emerging dominant severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants enables policymakers and vaccine makers to get prepared for future waves of infections. The last three waves of SARS-CoV-2 infections caused by dominant variants, Omicron (BA.1), BA.2, and BA.4/BA.5, were accurately foretold by our artificial intelligence (AI) models built with biophysics, genotyping of viral genomes, experimental data, algebraic topology, and deep learning. On the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 41 publications
(69 reference statements)
1
22
0
Order By: Relevance
“…The five dominant VOCs that have been reported so far (as of November 2022) are alpha (B.1.1.7), beta (B.1.351), gamma (P.1), delta (B.1.617.2), and omicron (B.1.1.529) ([ 35 ], accessed on 24 November 2022). The first two variants (i.e., alpha and beta) were responsible for the peak of COVID-19 infections and deaths from October 2020 to the beginning of summer 2021 (depending on the area), while the third variant (i.e., gamma) was mainly circulated during the same period in Brazil and L. America [ 36 ]. The third wave of COVID-19 was caused by the fourth variant, named delta, which circulated from April 2021 until the end of the year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The five dominant VOCs that have been reported so far (as of November 2022) are alpha (B.1.1.7), beta (B.1.351), gamma (P.1), delta (B.1.617.2), and omicron (B.1.1.529) ([ 35 ], accessed on 24 November 2022). The first two variants (i.e., alpha and beta) were responsible for the peak of COVID-19 infections and deaths from October 2020 to the beginning of summer 2021 (depending on the area), while the third variant (i.e., gamma) was mainly circulated during the same period in Brazil and L. America [ 36 ]. The third wave of COVID-19 was caused by the fourth variant, named delta, which circulated from April 2021 until the end of the year.…”
Section: Resultsmentioning
confidence: 99%
“…BQ.1.1 is another sublineage of the original BA.5 variant and exhibits high potential to replace BA.5 and become the new dominant variant. Based on modeling estimates, by the beginning of 2023, more than 80% of COVID-19 cases are expected to be due to BQ.1/BQ.1.1 SARS-CoV-2 variants [ 18 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…This would proficiently help develop rational predictive models of the effect of future variants and even design possible new antigens for vaccine update. Work in this direction has been carried out using extensive sequence information and ML to predict new evolutionary variants. …”
Section: Discussionmentioning
confidence: 99%
“…The biggest challenge with respect to managing the burden of COVID-19 is the continuous evolution of SARS-CoV-2 [16]. In particular, the emergence of the Omicron variants of the virus has significantly changed the landscape, and whereas previously there had been a sequential emergence of single predominant variants, we are now in the era of a pool of codominant variants [17, 18]. As of January 2023, the most recent Omicron subvariants of concern include XBB.1.5, BQ.1, and BQ.1.1 [19], and it has been shown that some monoclonal antibodies, including bebtelovimab, tixagevimab/cilgavimab, and casirivimab, lose their ability to neutralize these subvariants in vitro [20].…”
Section: Introductionmentioning
confidence: 99%